Deciphering Consistency and Coherence in U.S Foreign Policy: North Korea under Trump and Biden - Taim, Adam (Journal of International Relations, 2024)
Propose: This study investigated how consistent and coherent U.S. foreign policy toward North Korea was under President Trump and Biden. Methodology: Through qualitative analysis of policy shifts and diplomatic strategies, this paper explored how effectively both administrations advanced their policy objectives within the intricate dynamics of U.S.-North Korea relations. Data were collected from primary sources like official government documents and secondary sources like academic journal articles and media reports. Thematic and content analyses were employed to identify recurring motifs and evaluate the articulation and implementation of policy strategies. Findings: Findings indicated that Trump's untraditional approach of involving North Korean leader Kim Jong-un directly, alongside a "maximum pressure" campaign, yielded mixed outcomes. While it broke long-standing diplomatic deadlocks, it faced challenges such as inconsistencies and limited progress on denuclearization. In contrast, Biden's administration focused on multilateralism, alliance-building, and a structured policy framework. Nonetheless, it also encountered several challenges in making tangible progress toward denuclearization. The study underscored the importance of future U.S. administrations integrating the strengths of both approaches to enhance foreign policy effectiveness. Unique Contribution to Theory Practice and Policy: This study improved understanding of contemporary international relations by dissecting American interactions with North Korea under two different administrations. It provided crucial insights for policymakers, highlighting how maintaining consistency and coherence is pivotal in forming effective foreign policy.